Analisis Dampak Transformasi Digital Terhdap Profesi Akuntansi: Perspektif Peran Strategis Akuntan Dan Adaptasi Teknologi - Samihah Ulvah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation has fundamentally reshaped the accounting profession by integrating advanced technologies such as artificial intelligence, big data analytics, cloud computing, and robotic process automation into financial processes. This study analyzes the impact of digital transformation on the accounting profession, focusing on the evolution of accountants’ strategic roles and required technological adaptation through a qualitative, non-empirical systematic literature review. The results indicate that digital transformation enhances efficiency, accuracy, and real-time reporting while shifting accountants’ roles from transactional record keepers to strategic advisors and data analysts. However, this transformation introduces multidimensional challenges, including digital skill gaps, resistance to change, cybersecurity risks, and ethical concerns related to algorithmic bias and data governance. The findings highlight that successful digital transformation depends on the integration of technological capabilities, professional competencies, and adaptive regulatory frameworks.